Társadalmi konfliktusokat generáló ökológiai történések a Balaton életében az utóbbi néhány évtizedben – Halpusztulások - Takács, Péter; Turcsányi, Béla; Bíró, Péter (Acta Scientiarum Socialium, 2013)
Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Mass Fish Kills In this paper we summed up the history and causes of the mass fish kill events documented at Lake Balaton during the last 50 years. The first catastrophic fish kill (resulting in 500 t dead fish) was caused by the leaching of PCBs used on the catchment area of the lake in 1965. From the 1970s to the end of the ’90s, in parallel with the increasing eutrophication fish kills became more frequent, which impacted the whole fish fauna and spread over the lake. In the last years with the ongoing oligotrophication the mass kills terminated. Only sporadic species specific deaths were registered.
Keywords: water-pollutions; eutrophication; overexploitation